Central adiposity increases the odds for plasma folate deficiency among Chinese women of reproductive age - Zhang, Jinjuan; Du, Yushan; Che, Xiaoyu; Xia, Shuangbo; Zhang, Le; Liu, Jufen (Frontiers in Public Health, 2022)
Objective: To explore whether central adiposity was at higher plasma folate deficiency risk than general adiposity among nonpregnant reproductive women in China. Methods: A cross-sectional survey on nutritional status among nonpregnant women aged 18–30 years in 2005–2006 in China was conducted. General adiposity was defined as body mass index (BMI)≥24 kg/m2, and central adiposity as waist circumference>80cm. Plasma folate concentration <10.5 nmol/L (measured through microbiological assay) was defined as plasma folate deficiency. Odds ratios (OR) and 95% confidence intervals (CI) for plasma folate deficiency were calculated using a logistic regression model, with adjustment for potential confounders. Results: A total of 3076 nonpregnant women aged 18–30 years were included in the final analysis. Compared to women with normal BMI and WC, women with both general and central adiposity had the highest risk for plasma folate deficiency (OR=3.075, 95% CI: 1.762–5.368). Women with exclusively central adiposity had an excess risk for plasma folate deficiency (WC>80 cm, BMI<24 kg/m2; OR=3.054, 95% CI: 1.388–6.719), which was higher than women with exclusively general adiposity (BMI≥24 kg/m2, WC≤80 cm; OR=1.732, 95% CI: 1.260–2.380). Combined use of BMI and WC can detect more women (11.7%)) at higher plasma folate deficiency risk than either used alone. Conclusions: Women with central adiposity in normal weight has higher risk for plasma folate deficiency than general obesity only. Early screening for central adiposity among reproductive women would be meaningful to prevent folate deficiency and improve life-cycle health.